The Process of Improving the Spiritual Environment in the Educational Process - Boltaeva Muhayyo; Boyzakova Umida (Researchparks Publishing, 2022)
This article covers the emergence of the spirituality of the Uzbek nation from ancient times, its historical foundations, evolutionary stages, and the role of scientists and heads of state in the development of national spirituality on scientific grounds.